University Teachers’ Engagement in Academic Writing in Nepal - Khanal, Bishnu; Devkota, Kamal Raj; Acharya, Kamal Prasad; Kandel, Rajan Kumar; Chapai, Krishna Prasad Sharma; Joshi, Dirgha Raj (Pragyaratna प्रज्ञारत्न, 2025)
This research investigates the engagement of university teachers in research and publication activities at Tribhuvan University (TU) in Nepal. Utilizing a cross-sectional survey design, quantitative data from 473 teachers across 23 TU colleges were analyzed using the chi-square test Ficher’s exact test, and binary logistic regression. The results reveal a notably low level of engagement in research and publication activities among teachers. Teachers publish fewer papers in international/indexed journals compared to national journals. Urban location and Quality Assurance and Accreditation (QAA) certification correlate with higher engagement, contrasting with lower participation in rural settings, district towns, and non-QAA accredited institutions. The study recommends fostering an academic culture that motivates and empowers teachers for research and publication. Furthermore, gender, geographical location, and institutional type (QAA vs. non-QAA) are identified as significant factors shaping teachers’ research involvement and publications. <!–a=1–>